Digitalizing Coursebooks? Why Not - Lu’lu’ul Jannah; Yudi Basuki (STKIP PGRI Tulungagung, 2020)
As a matter of fact, in today digital era, the advancement of ICT (Information and Communication Technology) has shifted teaching-learning paradigm rapidly. The objective of the research is to develop a digital vocabulary coursebook (buku ajar) for Students of English language education department which can be applied on the smartphone. It is digitalized by using Adobe Flash CS6 Professional software with APK format. The smartphone that supports the application is android version 1.5 (cupcake) or above. The researchers design an educational RD research approach aimed at developing educational products, like curriculum, syllabus, textbooks, instructional media, etc. The subject of this research is the second semester of English language education department students of STKIP PGRI Trenggalek 2018/2019 academic year. The instruments used in this research are a questionnaire, interview, and observation. Those instruments of the data were analyzed in two different ways. The data collected by questionnaire was analyzed quantitatively, and data collected by observation and interview were analyzed qualitatively. Research findings show that the developed product which was based on students’ needs, the recent theory of vocabulary, RD, digitalizing and vocabulary coursebook which was also developed in five steps development resulted good responses from students in TLP of vocabulary subject in English language Education department. Mostly students agree that the digital book applied on their smart phone is indispensable necessity for today TLP which they may access it anywhere and anytime with ease. Besides, the product once also proves that digital material is more motivating, engaging and fun than the conventional one.